Estudo do comportamento dos fluidos em um protótipo de um cadinho de Alto Forno durante o seu esgotamento - Alvares, Giancolli Cordoni Bellotto (Universidade Federal de São Carlos, 2019)
Steel is the science dedicated to the studies of steel production and treatment, such as obtaining metallic iron. The oldest processes for obtaining metallic iron were conducted in various types of furnaces, currently using the blast furnace. The blast furnace is essentially a huge countercurrent heat exchanger and a chemical reactor in which pig iron is produced by iron ore at temperatures above 1500 ° C, because of the high temperatures, refractory materials are always present. in their processes. Refractory materials are used because they support the aggressive environment of the steelmaking process, providing structural resistance to corrosion and also avoiding heat loss from steel to the medium. The condition of the blast furnace refractory is the main limiting factor for the life of a blast furnace. Also due to the high process temperatures it is necessary to use tools that simulate the behavior of the internal crucible fluids. Thus, the present undergraduate work with the aid of the Ansys Student v.19 - R2 tool, which uses the finite volume methods to solve the necessary equations, analyzed the behavior of the internal fluids during the emptying of a printed crucible prototype. 3D printer, varying the height of the liquids. Thus, we obtained profiles of: phases, velocities and turbulent kinetic energy over time, thus, it was possible to analyze how the fluids behave during the emptying of the crucible, the zones where the velocity and turbulent kinetic energy are more aggravating and the relevance of the dead man's presence.
Study of the behavior of fluids in a prototype of a blast furnace crucible during exhaustion
Keywords: Alto-forno; Fluidodinâmica Computacional; Cadinho; Blast furnace; Computational Fluid Dynamics; Crucible; ENGENHARIAS::ENGENHARIA QUIMICA